Pengaruh Faktor Fundamental Terhadap Harga Saham Pada Kinerja Keuangan Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Wanda Aprilianti; Ersi Sisdianto (Jurnal Bisnis Kreatif dan Inovatif, 2024)
The Indonesian economy is increasing every year, this cannot be separated from the contribution of the capital market (Indonesian Stock Exchange) which is increasingly active in driving Indonesian economic activity. Activity on the Indonesian Stock Exchange is supported by the increasing number of issuers issuing securities, especially share instruments. Improving stock trading conditions on the Indonesia Stock Exchange (BEI) is able to attract the general public to invest their excess funds in the stock market. The aim of this research is to determine the fairness of share prices and find out which companies are most suitable for investment by calculating the Price Earning Ratio (PER) and Price to Book Value (PBV). This research uses descriptive research with a quantitative approach. The population of this research uses Consumer Goods sector companies that are included in the Indonesian Sharia Stock Index for the 2015-2016 period. Fundamental Analysis is an analysis that functions to estimate future share prices by estimating the value of company fundamental factors that influence future share prices. These factors include ROE, EPS, DPS, DPR, PER, and PBV. The intrinsic value of the stock will be seen whether the stock is smaller than the market value and is considered expensive (overvalued), the intrinsic value is greater than the market value and is considered cheap (undervalued) or the intrinsic value is the same as the market value meaning it is valued fairly (correctly valued). The results of this research show that 9 out of 16 companies are undervalued and only the companies Taisho Pharmaceutical Indonesia Tbk and Chitose Internasional Tbk whose share prices are undervalued are supported by advanced PER and PBV calculations, the decision that can be taken is to buy these shares.